Synthesis and Properties of N-Hydroxy-N-o-(Chloro) Phenyl-N'-(3-Methyl) Phenyl-p-Toluamidine Hydrochloride - Khan*, Shabaz; Hemlata Mohabey†, Ms. (Asian Journal of Chemistry, 2010)
N-Hydroxyamidines are versatile reagents for inorganic analysis. In thepresent communication a new hydroxyarnidine hydrochloride N-hydroxy-N-o-(chloro)-phenyl-N'-(3-methyl)-phenyl-p-toluamidine hydrochloridehas been synthesised and characterised on the basis of m.p., elementalanalysis, UV and IR spectra. The ultraviolet spectra of the compound in95% ethanol shows three distinct bands at 208, 256 and 314 nm. Theinfrared spectra of the compound shows bands at 3250, 3030, 2550, 1610and 930 cm-1 for v(O—H), C—H (aromatic stretch), v(C=O) andv(N—O) absorption respectively. The compound, like other reportedhydroxyamidines, reacts with vanadium(V) in presence of acetic acid andforms violet-coloured, chloroform-soluble complex. A new method hasbeen developed for extraction and spectrophotometric determination ofvanadium(V) and has been successfully applied for the determination ofvanadium in Bayer liquor. Most of the common ions generally associatedwith aluminium oxide do not interfere in the determination.